1986
DOI: 10.1088/0022-3719/19/30/013
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared studies at intermediate magnetic fields with the neutral shallow donors in GaAs and InP of transitions not involving the ground state

Abstract: More than thirty sharp lines are observed in the far-infrared photoconductivity from the neutral shallow donors in n-GaAs and InP at wavelengths longer than the longest wavelength that will excite electrons from the ground (1s) state of the donor. Twenty-four of the lines observed can be positively identified as corresponding to transitions given by p to q where p and q are the principal quantum numbers involved and are given by 2, 3 and 4. The n=2 to 2 lines involving the 2s state (2p--2s, 2s-2p+, 2s-2p0) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In the past decade, there has been increasing interest in the properties of negatively charged donors (D − centers) in quasi-two-dimensional (2D) systems, particularly in quantum wells (QWs) [1][2][3][4][5][6][7][8][9][10][11][12][13] and in quantum dots (QDs). 14,15 The D − centers can be formed in bulk semiconductors only under metastable conditions, 2 however, in semiconductor heterostructures these are readily formed because of the dramatic increase of the D − binding energy as a consequence of the spatial confinement, which is even further increased by the application of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, there has been increasing interest in the properties of negatively charged donors (D − centers) in quasi-two-dimensional (2D) systems, particularly in quantum wells (QWs) [1][2][3][4][5][6][7][8][9][10][11][12][13] and in quantum dots (QDs). 14,15 The D − centers can be formed in bulk semiconductors only under metastable conditions, 2 however, in semiconductor heterostructures these are readily formed because of the dramatic increase of the D − binding energy as a consequence of the spatial confinement, which is even further increased by the application of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the on resonance data using a three-state model depicted in the inset of Fig, 1, The rate equations are (1) where 11, nd< n~, are the concentrations of electrons in the conduction band, the Is ground state, and the 2p+ state, respectively. The absorption cross sections of the Is-free carrier and ls-2p+ transitions are O'c and O'r respectively, Fis the photon flux density llw) of the circular polarization of FIR causing each transition, Each transition couples to opposite circular polarizations, although the FIR impinging onto the sample was unpolarized, 'Ii 1 is the rate at which electrons relax from the 2p+ state to the ground state while remaining bound to the donor andX~ is the rate at which the electrons get ionized from the 2p + level.…”
Section: Department Of Physics and Center For Free Electron Laser Stumentioning
confidence: 99%
“…Experimental verification of the existence of the D Ϫ singlet ground state in bulk GaAs was first obtained through far-infrared ͑FIR͒ magnetoabsorption studies reported by Armistead et al 4 These investigations, which agreed qualitatively with the earlier theoretical predictions of Larsen 5,6 and with the later calculations of Pang and Louie, 7 suffered, however, from a combination of material-and experimental technique-related problems that strictly limited these studies to the observation of relatively broad D Ϫ bands in a restricted number of compensated samples. More recent efforts 7-11 have used quantum-well ͑QW͒ geometries to study two-dimensional ͑2D͒ D Ϫ singlet states that produce more measurable but rather broad D Ϫ spectral signatures.…”
mentioning
confidence: 99%
“…Hence, identification of D Ϫ features in a given FIR absorption spectrum is not straightforward, relying on comparisons with quantitative theoretical predictions, and has often been controversial. 4,[7][8][9][10][11] The situation is even more difficult in the case of higherlying states of the D Ϫ center, which can become bound in the presence of a magnetic field. It has been predicted for some time that the application of a magnetic field could bind additional D Ϫ ͑and H Ϫ ) states, such as the 1s spin triplet.…”
mentioning
confidence: 99%